First-Person Encounters #2: Satyajit Chakaborty - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our second podcast where we interview Satyajit Chakraborty, a game developer, game designer and researcher. He also founded Flying Robots Studios in 2012 and has made various unique games. Here he talks about his first experiences with gaming in India.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé